Knowledge and healthcare-seeking behavior of family caregivers of children with pneumonia: A qualitative study in an urban community in Indonesia - Nyimas Heny Purwati (Belitung Raya Foundation, 2021)
Background: Childhood pneumonia is the leading cause of death. Family caregivers may have a poor understanding of pneumonia, especially related to prevention and treatment. It is crucial to understand country-specific knowledge and healthcare-seeking behaviors of caregivers of children with pneumonia before planning programmatic responses, particularly in an urban community where the culture-social economic status is diverse.